2014
DOI: 10.18632/oncotarget.1744
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of bladder cancer and prediction of survival by urinary metabolomics

Abstract: Bladder cancer (BC) is a common cancer but diagnostic modalities, such as cystoscopy and urinary cytology, have limitations. Here, high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (HPLC-QTOFMS) was used to profile urine metabolites of 138 patients with BC and 121 control subjects (69 healthy people and 52 patients with hematuria due to non-malignant diseases). Multivariate statistical analysis revealed that the cancer group could be clearly distinguished from the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 37 publications
9
130
1
Order By: Relevance
“…However, these investigators did not report the identities of these metabolites. Separate studies have also suggested the association of acylcarnitines with bladder cancer [36], [37], as well as with esophageal squamous cell carcinoma [38]. Since our results also reveal that acylcarnitines are significantly elevated in HNSCC, this class of metabolites may have potential as a biomarker for epithelial-derived cancers.…”
Section: Discussionsupporting
confidence: 71%
“…However, these investigators did not report the identities of these metabolites. Separate studies have also suggested the association of acylcarnitines with bladder cancer [36], [37], as well as with esophageal squamous cell carcinoma [38]. Since our results also reveal that acylcarnitines are significantly elevated in HNSCC, this class of metabolites may have potential as a biomarker for epithelial-derived cancers.…”
Section: Discussionsupporting
confidence: 71%
“…This result reflected the increased conversion of citrate into fatty acids necessary for β-oxidation to support the rapid proliferation of cancer cells. Numerous disorders have been described that lead to disturbances in energy production and intermediary metabolism, which are characterized by the abnormal levels of acylcarnitines and citrate164142. This also implies a single metabolite will have limited use for an accurate diagnosis of BC, however, the biomarker panel would be more specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 33 metabolites had a potentially useful diagnostic value with the AUC above 0.7, and 11 metabolites had a good diagnostic value with the AUC above 0.8 (Supporting Information Table S7). 17 Multivariate ROC curve-based exploratory analysis was carried out (http:// www.metaboanalyst.ca/faces/Secure/upload/RocUploadView. 17 Multivariate ROC curve-based exploratory analysis was carried out (http:// www.metaboanalyst.ca/faces/Secure/upload/RocUploadView.…”
Section: Bca Biomarker Discoverymentioning
confidence: 99%
“…12 Although cytology is a noninvasive method and has a high specificity, its sensitivity is not satisfactory, particularly for low-grade tumors. 17 Wittmann BM et al analyzed urine metabolomics of 66 BCa positive samples using UHPLC-MS/MS and GC-MS. Most of the recent research efforts have been directed at discovery of BCa biomarkers using metabolomics technologies.…”
Section: Introductionmentioning
confidence: 99%